School Security in the Post-Columbine Era: Trends, Consequences, and Future Directions. (August 2019) - King, Sanna; Bracy, Nicole L.
Harsh and reactionary school security measures, including policing, surveillance technology, and emergency preparedness strategies increased substantially in the two decades following the mass shooting at Columbine High School in 1999. These strategies have limited empirical support for preventing violence in general and mass shootings, in particular. Instead, they have proven to be problematic, often doing more harm than good by criminalizing student misbehavior, contributing to negative school climate, and having psychological impacts on students' perceptions of safety. In recent years, many schools have started to explore promising alternative approaches, including threat assessment, positive behavioral interventions, restorative practices, and improving relationships between students and adults. This article reviews the trends in school security from the 1990s through the present, drawing on national data from the U.S. Department of Education and scholarly research on school security. Our specific focus will be on the changes in school security that have been made to prevent or minimize the impact of potential school shooters. We also discuss the consequences of the school security boom and the future directions to ensure school safety.